The Effect of Work Motivation on Employee Performance in the Production Department at PT GARUDA TOP PLASINDO in Surabaya - shindu dedali (Universitas Islam Lamongan, 2023)
PT GARUDA TOP PLASINDO in Surabaya expects a quality workforce along with technological developments and in line with efforts to motivate employees to improve their performance. Based on the research that has been carried out, the analysis obtained by the author is the relationship with work motivation on employee performance. From these problems, the authors write the problem is: